Legal Study of Building Sharia-based Investment in Aceh: The Challenges After the Enactment of the Qanun of Sharia Financial Institution - Yahya, Azhari; Yusri, Yusri; Adwani, Adwani; Adli, M.; Jafar, M. (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The presence of Aceh Qanun Number 11 of 2018 concerning Sharia Financial Institution (SFI) is an important breakthrough in building a Sharia-based economy in Aceh. This goes hand in hand with Aceh's privileges in implementing Islamic law as stipulated in the Aceh Qanun Number 8 of 2014 concerning Principles of Islamic Sharia. Hence, this research aims to scrutinize the challenges in building Sharia-based investments in Aceh after the enactment of the Qanun of SFI. This study was conducted using normative legal methods with statutory and Sharia economic law approaches. The data analyzed are literature and legal rules such as laws, qanuns, books, and articles related to the discussion. The results of this study indicate that there are several challenges occur in building Sharia-based investments in Aceh. Firstly, lack of understanding about SFI Qanun by stakeholders because not all of them have a full understanding of the contents of this Qanun. Secondly, limited access to financial resources that can be used by investors, and business actors to run their businesses. Thirdly, Aceh's low economic growth has resulted in low investors interested to invest in Aceh. This condition has a significant impact on the sustainability of Sharia-based investments in Aceh. Fourthly, inadequate infrastructure especially information technology infrastructure to support the implementation of the Qanun of SFI. Therefore, it is suggested to the Government of Aceh provide a better understanding of the Qanun of SFI at all levels of society. Then,  the government also needs to open access to financial resources for the investors and business actors who want to invest in Aceh. Besides, appropriate measures to increase economic growth in Aceh need to be taken promptly so that incoming investment may increase gradually. Finally, in the context of the Sharia economy, the existence of the LSK qanun is part of legal efforts for the benefit of all financial transactions in Aceh in accordance with Islamic Sharia values.